Potential application of peripheral blood biomarkers in intracranial aneurysms - Wu, Yangying; Zhao, Ziya; Kang, Shaolei; Zhang, Lijuan; Lv, Fajin (Frontiers in Neurology, 2023)
Intracranial aneurysm (IA) counts are increasing yearly, with a high mortality and disability after rupture. Current diagnosis and treatment rely on costly equipment, lacking effective indicators for progression prediction and specific drugs for treatment. Recently, peripheral blood biomarkers, as common clinical test samples, reflecting the immune and inflammatory state of the body in real-time, have shown promise in providing additional information for risk stratification and treatment in IA patients, which may improve their outcomes after aneurysm rupture through anti-inflammatory therapy. Therefore, this paper reviewed the progress of potential biomarkers of IAs, including inflammatory blood indicators, cytokines, and blood lipids, aiming to aid individual management and therapy of aneurysms in clinical practices.